(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1862)
Professor C Plazzi Smyth describes how he acquired a photograph of an illuminated copy of a missal that once belonged to Mary Queen of Scots that was held in the Hermitage in St Petersburg. Professor Smyth also provides details about the book’s dimensions, decoration, history and content. The photograph of the book is included in the article.